A Human Development Index by Income Groups - Mark Misselhorn; Stephan Klasen; Kenneth Harttgen; Michael Grimm (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2007)
One of the most frequent critiques of the HDI is that is does not take into account inequality within countries. We suggest a relatively easy and intuitive approach which allows to compute the three components and the overall HDI for quintiles of the income distribution. This allows comparisons of the level in human development of the poor and non-poor within and across countries. An empirical illustration shows large discrepancies in human development within countries especially in Africa. These discrepancies are lower the higher the HDI, but only weekly so. Inequality in income is generally higher than inequality in education and life-expectancy.
Keywords: 330; Human Development; Income Inequality; Differential Mortality; Inequality in Education